Pengungkapan Pendapatan Non Halal pada Laporan Keuangan Bank Umum Syariah - Sholihah, Ria Anisatus (AKTSAR: Jurnal Akuntansi Syariah, 2021)
Islamic Bank as a type of Islamic financial institution has the authority to collect and distribute funds to the public. In carrying out its operational activities, Islamic Banks have transactions that can lead to non-halal income because Islamic Banks also make transactions with Conventional Financial Institutions. PSAK 101 has regulated the disclosure of no n-halal income as part of the Report on the Sources and Use of Virtue Fund. The purpose of this study is to determine the description and disclosure of non-halal income in the financial statements of Islamic Commercial Banks. This study uses a qualitative research method with a descriptive approach. The subjects of this study were 14 Islamic Commercial Banks operating nationally and publishing complete financial reports in 2019 on the official website of Islamic Commercial Banks. The results showed that non-halal income from 14 Islamic Commercial Banks have been disclosed in accordance with PSAK 101, namely the Report on the Sources and Use of Virtue Funds. However, not all banks disclose in detail the reasons for the occurrence and use of non-halal income in the Notes to Financial Statements.